Study on the mechanical behavior of silica nanoparticle reinforced magnesium bio-nanocomposite - Norfatihah, Ismail (2022)
In recent years, the need for advanced metallic biomaterials for artificial implants has gradually risen and the market for people with bone fractures and degeneration attributable to collisions, athletic injuries or normal ageing processes, often requiring biomaterial implants to regain function, is expected to continue. Magnesium (Mg) and its alloys have drawn tremendous interest in becoming possible alternatives to traditional orthopaedic implant materials due to their excellent biodegradable and mechanical properties. These Mg materials demonstrate low corrosion resistance in a physiological environment despite their great benefits. In order to improve corrosion behaviour and sustain degradation at a controlled rate, filler materials are applied to the Mg alloys to produce composites. Apart from other oxide materials, silica (SiO2) is another option of filler material that can be used to produce Mg-based bio-composite due to its high biocompatibility. Mechanical alloying (MA) technique has been widely used in the manufacturing of composite materials, requiring the transformation of materials due to various cold welding, fracturing and re-welding processes of milled powder particles in a highly energetic ball mill, making the powder more homogeneous due to its ability to integrate the reinforcing particle into the metal matrix at a close distance. Therefore, in this study, magnesium- nanosilica (Mg-SiO2) composite system has been fabricated by the mechanical alloying process with different weight percentages of nanosilica reinforcement in order to achieve an optimal reinforcement composition. In order to get the formulation, the raw powders with the desired percentage were blended, compacted and sintered. The fabricated samples were then prepared for microstructural characterization, mechanical and corrosion testing. Analysis of the microstructure revealed an almost flawless microstructure of nanocomposite samples with a new phase of magnesium silicide formation (Mg2Si). Mechanical properties of the composites, including hardness and tensile strength, have been examined. It is observed from the obtained mechanical properties that the hardness and tensile strength of the nanocomposites improve dramatically due to the production of the Mg2Si phase in the composite. In addition, the fabricated nanocomposite has stronger corrosion resistance properties than the pure Mg material. The addition of 5 wt. % nanosilica into the Mg matrix reveals superior mechanical and corrosion properties relative to the matrix material and other compositions of the Mg-SiO2 nanocomposites. This Mg-5%SiO2 nanocomposite demonstrated its potential to be an effective bio-implant material.